PENGARUH LATIHAN VISUALISASI DAN KEPERCAYAAN DIRI TERHADAP PRESTASI ATLET UKM PANAHAN UNNES - Elhaqe, Qintarazany Marayattaqiezza (Unnes Journal of Sport Sciences, 2021)
Mental training must be essential for archery athletes as archery is an individual sport. However mental training is still being neglected in any archery training program. The purpose of this research is to determine the effect of visualization training and confidence on the achievement of athletes of student activity unit in UNNES. This research is using an experimental research with One Group Pretest and Posttest design. The instrument used is confidence questionnaire and archery score result test. The research subject is nine archery athletes of student activity unit in UNNES. Data analysis technique uses regression test and paired sample t-test. The result of regression test, the value (sig) 0,009 < 0,05 and the paired sample t test archery score results is t count 2,573 > t table 1,860 with significant level 0,033 < (0,05). As for the self confidence data the value t count 4,203 > t table 1,860 with significant level is 0,003 < 0,05. Based on calculation, it is concluded that 1) there is an effect of visualization exercises on athlete achievement, 2) there is increase in self confidence on achievement results in archers. Advice: 1) for archers who have low self confidence level and score test result can be fixed by using visualization exercises, 2) for coach to pay more attention to the form of mental training, 3) to researchers can do research with a wider samples and add comparison variables.